Lithology and Groundwater Geochemistry of Beulah and Marshay Townships - Booty, William G. (My University, 1977)
A study was carried out during 1976 to determine the lithological and hydrological factors that are involved in controlling the water chemistry of the lakes in Beulah and Marshay Townships; approximately 60 miles north of Sudbury, Ontario. There are several lakes with water quality characteristics totally analogous to a calcareous terrain dispersed among lakes with water quality typical of an igneous terrain.
The results indicate that:
(1) the surficial (1-10 m) glacial drift is not the source of the high levels of Ca²⁺, Mg²⁺, and HCO₃¯ found in the carbonate lake waters. The surficial glacial drift units have been derived from dominantly granitic terrain and are probably of local origin;
(2) in the study area, non-transient, basal groundwater is the major transport mechanism for the major ions present in the carbonate lakes;
(3) the carbonate material is a mixture of calcite and dolomite. It appears to be located 15-20 m below the surface;
(4) lakes saturated with respect to calcium carbonate are deep enough and topographically low enough to intersect the calcareous material and/or the basal groundwater that flows through the carbonate material. The other lakes receive their major ions from the dissolution of silicates in the surficial glacial drift;
(5) recent calcareous sediments on the shoals of Shoofly Lake have been produced by the physical and chemical breakdown of the aragonite shells produced by the pelecypods and gastropods living on the shoals. This process is active at present.
Keywords: Geology; Geology